Faking reality - Fujimura, Sara (New York : Tor Teen, an imprint of Tom Doherty Associates, 2021)
A Japanese American teen influencer balances her real life and online persona when her family$1 (Bs home renovation show takes a personal turn.s
Includes acknowledgments and author$1 (Bs note.s
Keywords: Reality television programs -- Fiction; Social media -- Fiction; Japanese Americans -- Fiction; Young adult fiction